Early lymphocyte recovery predicts superior overall survival after unmanipulated haploidentical blood and marrow transplant for myelodysplastic syndrome and acute myeloid leukemia evolving from myelodysplastic syndrome. Issue 12 (December 2013) - Chang, Ying-Jun; Zhao, Xiang-Yu; Xu, Lan-Ping; Liu, Dai-Hong; Liu, Kai-Yan; Chen, Yu-Hong; Wang, Yu; Zhang, Xiao-Hui; Zhao, Xiao-Su; Han, Wei; Chen, Huan; Wang, Feng-Rong; et al.
Abstract We investigated whether early lymphocyte recovery, after unmanipulated, haploidentical, blood and marrow transplant (HBMT), affected clinical outcomes in 78 patients with myelodysplastic syndrome (MDS) or acute myeloid leukemia evolving from MDS. Lymphocyte recovery was based on the absolute lymphocyte count on day 30 (ALC-30). Patients with high ALC-30 (≥ 300 cells/μL) had lower relapse rates (13.8% vs. 35.5%, p = 0.049) and lower incidence of bacterial infections (3.4% vs. 25.8%, p = 0.015) than those with low ALC-30 values. Multivariate analysis showed that a high ALC-30 was associated with improved overall survival (OS, hazard ratio [HR]: 0.099, 95% confidence interval [CI]: 0.029–0.337; p < 0.0001), improved leukemia-free survival (HR: 0.245, 95% CI: 0.112–0.539; p < 0.0001), lower relapse rate (HR: 0.096, 95% CI: 0.011–0.827; p = 0.033) and lower transplant-related mortality (TRM, HR: 0.073, 95% CI: 0.016–0.324; p = 0.001). Combinations of three mismatches in the human leukocyte antigen loci were associated with a higher TRM (HR: 5.026, 95% CI: 1.392–18.173; p = 0.014). Our results suggest that the ALC-30 can predict a favorable OS after unmanipulated HBMT.